Respuestas
Respuesta dada por:
6
.・✫Holiwi.✫・•
Vamos a resolver teniendo en cuenta la ley de los signos
Resolver:
[14-(12-5-6]+[-15+(4-3)]
14−(12−5−6)−15+4−3
=14−(7−6)−15+4−3
=14−1−15+4−3
=13−15+4−3
=13−15+1
=13+−14 → (+) (-) =(-)
=−1 → Respuesta.
Att: mitzu ツ
Respuesta dada por:
1
Respuesta:
.・✫Holiwi.✫・•
Vamos a resolver teniendo en cuenta la ley de los signos
Resolver:
[14-(12-5-6]+[-15+(4-3)]
14−(12−5−6)−15+4−3
=14−(7−6)−15+4−3
=14−1−15+4−3
=13−15+4−3
=13−15+1
=13+−14 → (+) (-) =(-)
=−1 → Respuesta.
Att: mitzu ツ
Explicación paso a paso:
Preguntas similares
hace 4 años
hace 4 años
hace 7 años
hace 8 años